Hadith #2694 - Sunan Abi Dawud - Abu Talha Ansari; Anas ibn Malik; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) then said: Return to them (Hawazin) their women and their sons. If any of you withholds anything from this booty, we have six camels for him from the first booty which Allah gives us. The Prophet (ﷺ) then approached a camel, and taking a hair from its hump said: O people, I get nothing of this booty, not even this (meanwhile raising his two fingers) but the fifth, and the fifth is returned to you, so hand over threads and needles. A man got up with a ball of hair i
Grade: Hasan

Hadith #4152 - Sunan Abi Dawud - Abu Talha Ansari; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Sa'id bin Yasar, Abu al-Hubab سعيد بن يسار أبو الحباب; Suhayl bin Abi Salah سهيل بن أبي صالح; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
The Prophet (ﷺ) said: The angels do not enter a house which contains a picture, a dog, or a man who is impure by sexual defilement.
Grade: Hasan

Hadith #4154 - Sunan Abi Dawud - Abu Talha Ansari; al-Laith bin Sa'd الليث بن سعد; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
I said: Mother, he has told me that the Prophet (ﷺ) has said: He also said the words ; Sa’id b. yasir client of Banu al-Najjar.
Grade: Sahih

Hadith #4882 - Sunan Abi Dawud - Abu Talha Ansari; al-Laith bin Sa'd الليث بن سعد; Ishaq bin al-Sabah al-Kundi إسحاق بن الصباح الكندي الأشعثي; Isma'il bin Basheer إسماعيل بن بشير مولى بني مغالة; Jabir ibn 'Abdullah; Sa'id bin Abi Maryam سعيد بن أبي مريم (Sunan Abi Dawud)
Everything of a Muslim is sacred to a Muslim : his property, honour and blood. It is enough evil for any man to despise his brother Muslim.
Grade: Sahih